Integrasi Nilai-Nilai Islam Dalam Etika Profesi Bimbingan Konseling - Akhir Pardamean Harahap; Amalya Asyfa; Putri Annisa purba; Mhd Arifin; Lestari Yunsiska Parhusip; Nabila Harahap; Mira Wulandari; Cinta Mollyka Rambe; Marwansyah; Kiki Nur Halijah Selian; Putri Wulandari; Ahmad Jibril; Putra Doli Arifin; Al Fariz Ahmad; Yuda prasetiyo (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This article discusses the integration of Islamic values ​​in the professional ethics of counseling guidance. In an era of globalization full of moral and ethical challenges, the guidance and counseling profession plays an important role in forming individual characters with integrity. Islamic values ​​such as honesty, justice, compassion and responsibility not only provide a moral foundation for counselors but also provide comprehensive guidance in carrying out their professional duties. This research explores the understanding and implementation of Islamic values ​​by counselors, identifying the challenges faced, as well as the benefits obtained from this integration. The research results show that counselors who integrate Islamic values ​​in their practice tend to provide more empathetic, fair and responsible services, which ultimately improves client well-being. However, there are challenges such as lack of training and differences in client backgrounds that need to be overcome. This article also provides practical suggestions for increasing the integration of Islamic values ​​in the ethics of the counseling profession, including curriculum development, regular training, and strengthening the professional community. Thus, the integration of Islamic values ​​in the professional ethics of counseling guidance is expected to have a significant positive impact on counselors, clients and society as a whole.